(3QSGdI fahS GdehMOjf GdeeQVI dbdhH GdebUQjf GdLGMOjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdMb hRQkG def EYJUe HYRGFeI hYbhOg s
(3BNQgG (B:s
(3aGSLOhG ddg hGYHOhG aeG Ydi GdQShd GdSGOb Shi GdHdGZ GdeHjf hGdMeO ddg QH GdYGdejf hSdGeI Ydi bGFe GdMb hdi GdOjf hGdMeO dehdGfG hMOg dGTQjc dg hdG eYHhO ShGg JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B58s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds